2024
DOI: 10.1038/s41541-024-00845-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on gene-deleted live-attenuated African swine fever virus vaccines

Hiep L. X. Vu,
D. Scott McVey

Abstract: African Swine Fever (ASF) is a highly lethal viral disease in swine, with mortality rates approaching 100%. The disease has spread to many swine-producing countries, leading to significant economic losses and adversely impacting global food security. Extensive efforts have been directed toward developing effective ASF vaccines. Among the vaccinology approaches tested to date, live-attenuated virus (LAV) vaccines produced by rational deleting virulence genes from virulent African Swine Fever Virus (ASFV) strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 120 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the mutant obtained by deleting these six genes in HLJ/18 was completely attenuated in virulence and induced complete protection against the parental potent virus. However, it has been reported that the vaccine candidates (HLJ/18-6GD) reverted to virulence after six back-passages, and it remains unclear how this reversal occurred [ 89 , 90 ]. As the understanding of ASFV has grown, the LAVs that have developed have become more effective and stable in providing protection.…”
Section: Control Strategiesmentioning
confidence: 99%
“…Furthermore, the mutant obtained by deleting these six genes in HLJ/18 was completely attenuated in virulence and induced complete protection against the parental potent virus. However, it has been reported that the vaccine candidates (HLJ/18-6GD) reverted to virulence after six back-passages, and it remains unclear how this reversal occurred [ 89 , 90 ]. As the understanding of ASFV has grown, the LAVs that have developed have become more effective and stable in providing protection.…”
Section: Control Strategiesmentioning
confidence: 99%
“…The use of recombinant attenuated virus strains as potential vaccine candidates has recently increased [ 10 , 11 , 12 ]. Novel vaccine candidates were developed by deleting ASFV genes involved in the production of the disease in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been employed, which include inactivated, subunit, DNA, virus-vectored, and live-attenuated (LAV) ASF vaccines [ 11 ]. Among these approaches, inactivated and subunit vaccines are safe but do not induce protective immunity [ 12 , 13 , 14 ] while live-attenuated (LAV) ASF vaccines are the most promising and exhibit a wide range of safety and efficacy against ASF [ 15 ]. Although it poses no threat to humans, ASF outbreaks can have a major effect on the pork sector, resulting in national and international restrictions on trade, affecting food security, and leading to major financial economic losses.…”
Section: Introductionmentioning
confidence: 99%